REVIEW: PENGARUH PERBEDAAN EKSIPIEN BINDER PADA TABLET PARACETAMOL TERHADAP WAKTU HANCUR DAN PELEPASAN OBAT - Iqbal Nurwahid,; Alfia Mujahra,; Muhammad Zairullah,; Riska Hidayah,; Helsy Indarwati,; Nor Latifah, (Jurnal Cakrawala Ilmiah, 2024)
This study aims to evaluate and compare the effectiveness of natural and synthetic binders in paracetamol tablet formulation, focusing on sweet potato starch, pregelatinized cassava, and pectin as natural binders, as well as synthetic binders commonly used in the pharmaceutical industry. The method used in this study is a literature review, by collecting, analyzing, and synthesizing various relevant previous research results regarding the effect of binders on the physical properties of tablets and drug dissolution rates. Based on the literature analysis, it was found that natural binders, such as pregelatinized starch and pectin, showed comparable or even better results in several parameters, such as disintegration and drug release, compared to synthetic binders. Pregelatinized starch, in particular, showed a faster dissolution rate, while pectin gave good results in terms of tablet hardness and friability. In addition, natural binders are more economical and environmentally friendly than synthetic materials.